Affirmative Action Study on the Political Rights of Women in the Indonesian Constitution - Malika Rajan Vasandani; Dwi Putra Nugraha; Susi Susantijo (The Constitutional Court of the Republic of Indonesia, 2022)
As the world’s third largest democracy, Indonesia’s governmental system should ideally function as a government of the people, by the people, for the people, to borrow the famous words of Abraham Lincoln. In reality, the House of Representatives of the Republic of Indonesia, an institution which should best represent the nation’s people in carrying out its duty of drafting legislative products, still fails to do so, as it is dominated by men. Deep-rooted patriarchal beliefs cloud the nation, while inadequate and inefficient laws have also contributed to the present situation of low female representation in politics. This article therefore looks into the effectiveness various laws and regulations intended to protect women’s political rights. It assesses the effect of the low participation of women on the quality and gender-sensitivity of laws passed by the House of Representatives. It also evaluates the urgency to introduce affirmative action policies through the 1945 Constitution to increase women’s participation rates. The authors have used the normative-empirical method, consisting of a statutory, conceptual and comparative approach. Materials used for this research include interviews with prominent figures, analysis of the law and a comparative study. Through this approach, the article concludes that prevailing regulations in Indonesia require improvement, as there needs to be a shift from the present quota system to a system of reserved legislative seats in order to reap the benefits of equal participation.